Investigating the Mediating Role of Cardiometabolic Traits in the Causal Link Between SHBG Levels and Stroke Risk via Network Mendelian Randomization - Peijiang Pan; Hao Liang; Mingli Li (Current Issues in Molecular Biology, 2025)
The causal nature of sex hormone-binding globulin (SHBG) in the pathogenesis of stroke remains uncertain. We explored whether SHBG levels are causally associated with stroke via cardiometabolic traits. A network two-sample Mendelian randomization (MR) study was conducted to determine the mediating roles of cardiometabolic traits in the causal effects of SHBG levels on stroke subtypes. Further two-sample MR analyses were performed to explore the inverse associations between significant cardiometabolic mediators and SHBG levels. The MR results indicated a protective effect of genetically increased SHBG levels on any stroke (odd ratio [OR] = 0.941; 95% confidence interval [CI]: 0.898, 0.984), any ischemic stroke (OR = 0.951; 95% CI: 0.922, 0.981), and small-vessel stroke (OR = 0.871; 95% CI: 0.765, 0.977). Moreover, genetically elevated SHBG levels were associated with lower waist circumference (WC, β = −0.091; 95% CI: −0.136, −0.046), waist-to-hip ratio (WHR, β = −0.057; 95% CI: −0.084, −0.030), triglycerides (TG, β = −0.188; 95% CI: −0.249, −0.127), systolic blood pressure (β = −0.799; 95% CI: −1.068, −0.530), and diastolic blood pressure (β = −0.436; 95% CI: −0.605, −0.267), and a reduced risk of type 2 diabetes mellitus (OR = 0.684; 95% CI: 0.400, 0.968) in both the discovery and replication datasets. The proportions of such cardiometabolic traits that mediated the causal effects of SHBG levels on any stroke, any ischemic stroke, or small-vessel stroke ranged from 17.8% to 52.7%; while the mediating effects of SHBG levels on the causal associations between WC, WHR, and TG and stroke ranged from 18.4% to 68.3%. Our findings suggest a protective effect of genetically elevated SHBG levels on stroke risk via key cardiometabolic mediators, primarily WC, WHR, and TG. The mediating roles of SHBG levels in the causal links from WC, WHR and TG to stroke risk were also established. These pathways support SHBG as a potential biomarker and therapeutic target in stroke prevention.